Domestic mindsets and early international performance: The moderating effect of global industry conditions - Nadkarni, Sucheta; Herrmann, Pol; Perez, Pedro David (Strategic Management Journal, 2011)
Abstract We develop and test a sensemaking model of early internationalization that ties domestic mindsets to international industry conditions and early international performance. Our central contention is that the fit between international industry conditions and domestic mindsets will lead to superior early international performance. We test this contention with a sample of 178 large and established domestic firms from 20 industries. Our results highlight the role of domestic mindsets in the early phases of internationalization and prescribe the types of domestic mindsets needed to maximize early international performance in global, multi‐domestic, and transnational industry conditions. Our results also provide valuable insights to top managers of large and established firms on how to reduce the risk of failure and how to successfully prepare for and cope with international environments by matching their domestic mindsets with international industry environments. Copyright © 2010 John Wiley & Sons, Ltd.